Droits écrits et droits coutumiers dans les Etats d’Afrique noire francophone aujourd’hui - Kenfack, Pierre Etienne (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
How should the states of French-speaking Black Africa articulate written and customary laws on their territories today? The question is not new, but it takes on another dimension if we consider traditional laws not as positive solutions that can be used, but from the point of view of their use as legal systems to create a common state law based on codification. This is what this contribution focuses on, highlighting the limits of the current articulation and suggesting one that gives customary law its rightful place.